The role of in-situ nano-TiB2 particles in improving the printability of noncastable 2024Al alloy - Tengteng Sun; Hongze Wang; Zhenyang Gao; Yi Wu; Mingliang Wang; Xinyuan Jin; Chu Lun Alex Leung; P.D. Lee; Yanan Fu; Haowei Wang (Materials Research Letters, 2022)
In-situ pre-decorated different content of TiB2 particle reinforced 2024 Al matrix composites (xTiB2/2024Al composite, x = 0, 1, 2, 4, 6, 8 wt.%) were printed by laser powder bed fusion (LPBF). A quantitative equation was established to quantify heterogeneous nucleating potency by TiB2 nanoparticles on the grain size of the LPBFed samples. Optimized mechanical properties were obtained in the as-printed 4TiB2/2024Al alloy which proved the feasibility of replacing the wrought part with the LPBFed one. This manuscript provides a method to determine the optimized content of TiB2 nanoparticles to change the noncastable material to the printable one.